A Unique Case of Cardiac Arrest following K2 Abuse - Saif Ibrahim; Farah Al-Saffar; Thomas Wannenburg (Case Reports in Cardiology)
Sudden cardiac death (SCD) accounts for up to 450,000 deaths every year in the United States (Zipes et al. (2006)). Most cases of sudden cardiac death occur in subjects with no prior history of heart disease (Myerburg et al. (1998)). The incidence of sudden death in a general population has been shown to increase contemporaneously with substance abuse (Phillips et al. (1999)). The causative association of sudden death with cocaine, methadone, and volatile agents is well established (Adgey et al. (1995) and Isner et al. (1986)). We describe a case of out-of-hospital cardiac arrest temporally related to abuse of the synthetic cannabinoid street drug known as K2. To our knowledge, there are no previously documented cases of sudden cardiac death associated with synthetic cannabinoids although they have been linked to myocardial infarction in teenagers despite normal coronary angiography (Mir et al. (2011)).